Non-sterilizing, Infection-Permissive Vaccination With Inactivated Influenza Virus Vaccine Reshapes Subsequent Virus Infection-Induced Protective Heterosubtypic Immunity From Cellular to Humoral Cross-Reactive Immune Responses - Choi, Angela; Ibañez, Lorena I.; Strohmeier, Shirin; Krammer, Florian; García-Sastre, Adolfo; Schotsaert, Michael (Frontiers in Immunology, 2020)
Conventional influenza vaccines aim at the induction of virus-neutralizing antibodies that provide with sterilizing immunity. However, influenza vaccination often confers protection from disease but not from infection. The impact of infection-permissive vaccination on the immune response elicited by subsequent influenza virus infection is not well understood. Here, we investigated to what extent infection-permissive immunity, in contrast to virus-neutralizing immunity, provided by a trivalent inactivated virus vaccine (TIV) modulates disease and virus-induced host immune responses after sublethal vaccine-matching H1N1 infection in a mouse model. More than one TIV vaccination was needed to induce a serum HI titer and provide sterilizing immunity upon homologous virus infection. However, single TIV administration provided infection-permissive immunity, characterized by lower viral lung titers and faster recovery. Despite the presence of replicating virus, single TIV vaccination prevented induction of pro-inflammatory cyto- and chemokines, alveolar macrophage depletion as well as the establishment of lung-resident B and T cells after infection. To investigate virus infection-induced cross-protective heterosubtypic immune responses in vaccinated and unvaccinated animals, mice were re-infected with a lethal dose of H3N2 virus four weeks after H1N1 infection. Single TIV vaccination did not prevent H1N1 virus infection-induced heterosubtypic cross-protection, but shifted the mechanism of cross-protection from the cellular to the humoral branch of the immune system. These results suggest that suboptimal vaccination with conventional influenza vaccines may still positively modulate disease outcome after influenza virus infection, while promoting humoral heterosubtypic immunity after virus infection.